A lightweight construction method for substation digital twin - GUO Jia; XIE Jinghai; SUN Mi; SU Dongyu; WANG Tao; YANG Youhang; WANG Shaorong (Diance yu yibiao)
The construction of substation digital twin is a key technology to realize the intelligence of substation operation monitoring and maintenance. In order to ensure the real-time mapping between substation physical entities and digital twin, a lightweight construction method of substation digital twin is proposed with practicality as the construction purpose and functional demand traction, and the idea of industrial computed tomography (CT) is introduced. And this paper focuses on how to construct the lightweight digital twin model of substation equipment. An improved 3D wireframe model is used to construct the skeleton of the substation digital twin. Texture mapping is performed on the 3D wireframe model of the substation to construct the local surface model of the substation digital twin. The tomography principle is used to construct a slice model reflecting the internal working conditions of the substation equipment. Among them, the 3D wireframe model of the substation is used for application navigation and provides coordinates for constructing the surface model and the slice model; the surface model is used for local appearance of the physical entity of the substation; the slice model is used for detailed characterization of the size and distribution of the physical parameters inside the physical entity of the substation equipment, and thus intuitively reflects the operating conditions of the electrical equipment of the substation. This paper elaborates the basic idea and the model construction principles of the proposed lightweight construction method for substation digital twin.